OPTIMIZATION AND IN VITRO EVALUATION OF CREAMS FORMULATION CONTAINING SPIRULINA (ARTHROSPIRA PLATENSIS) EXTRACT AND ZINC OXIDE NANOPARTICLES - WIKANTYASNING, ERINDYAH RETNO; ASTUTI, KARTIKA FIDI; NURHAKIMAH, ULIL FIKRI; SULA, RAMADHANI DWI (International Journal of Applied Pharmaceutics, 2021)
Objective: The aims of this study are to formulate creams containing combination of spirulina (Arthrospira platensis) extract and zinc oxide nanoparticles using glycerol and propylene glycol as humectants and to evaluate their physical characteristics and in vitro antioxidant activity. Methods: Spirulina was extracted by maceration method using methanol as solvent. The high energy ball milling technique was used to obtain zinc oxide nanoparticles. Creams were prepared in five formulas with the variations in the concentration of glycerol and propylene glycol. The physical characteristics of creams were evaluated including pH, spreadability, adhesiveness, and viscosity. The optimization was conducted by Simplex Lattice Design (SLD) method using Design-Expert software. In vitro antioxidant activity was evaluated using DPPH method. Results: The extraction resulted spirulina extract with a yield of 13.57%. The particle size of the ZnO nanoparticles obtained was 143.4±0.364 nm, with the polydispersity index of 0.177. Optimum formula of cream was obtained with the concentration of glycerol and propylene glycol was 12.9 and 17.1%, respectively. The spreadability, adhesiveness, viscosity, and pH of the optimized cream were 12.73±0.16 cm2, 1.47±0.12 s, 126.67±5.77 dPas, and 7.11±0.04, respectively. Cream containing spirulina extract and ZnO nanoparticles showed in vitro antioxidant activity with the IC50 value of 59.47±6.34 ppm. Conclusion: Cream, containing spirulina and ZnO nanoparticles, was successfully prepared using glycerol and propylene glycol as humectant and showed very strong antioxidant activity in vitro.